The Splendor and Opulence of the Past: Studying the Middle Ages in Enlightenment Catalonia - Freedman, Paul (Medieval Societies, Religions, and Cultures, 2023)
Keywords: bellpuig de las avellanes

Restoration of the arches in the cloister at the Monastery of St Mary of Bellpuig de les Avellanes - Solé, Ramon (Rescat: Centre de Restauració de Béns Mobles de Catalunya, 2017)
Keywords: bellpuig de las avellanes

A Privilege of Pope Innocent III for the Premonstratensian House of Bellpuig de les Avellanes - Freedman, Paul; Smith, Damian (Römische Historische Mitteilungen, 2014)
Siglenverzeichnis Bericht des Historischen Instituts beim Österreichischen Kulturforum in Rom für das Studienjahr 2011/2012 Astrid Larcher - Manuele Laimer, Ascoli Satriano, Gianera Piccola. Vorbericht zu den Grabungskampagnen 2010-2012 Paul Freedman - Damian Smith, A Privilege of Pope Innocent III for the Premonstratensian House of Bellpuig de les Avellanes Rudolf S. Stefec, Die Überlieferung der Deklamationen Polemons Petr Maťa, The false Orsini from over the Alps: Negotiating aristocratic identity in late medieval and early modern Europe Tomáš Černušák, Die Böhmische Kammer als Thema der Prager Nuntiatur zu Beginn des 17. Jahrhunderts Alessandro Metlica, Il Parnasso dell `Istro. Eugenio di San Giuseppe, Caramuel y Lobkowitz e la prima accademia italiana di Vienna (1657) Péter Tusor, Kardinalsnominierungen durch das Haus Habsburg im 17. Jahrhundert Rita Tolomeo, Potenze Protetrici e Unionismo nelle Terre Bulgare Andreas Gottsmann, "Warum lässt uns der Hl.Stuhl im Stich?" Die vatikanische Haltung zur Regierung Schuschnigg hinsichtlich Restauration und staatlicher Selbstständigkeit Inge Podbrecky, Gio Ponti in Wien. Das italienische Kulturinstitut im Palais Lützow-Fürstenberg Zusammenfassungen
Keywords: bellpuig de las avellanes

'Sancti Nicolai de Fontibus Amoenis' or 'Sti. Nicolai et Fontium Amenorum': The Making of Monastic History - Husband, Timothy (The Cloisters: Studies in Honor of the Fiftieth Anniversary, 1992)
Keywords: bellpuig de las avellanes

Four Tombs from Las Avellanas and Other Gothic Sculptures - Rorimer, James J. (The Metropolitan Museum of Art Bulletin, 1950)
Keywords: bellpuig de las avellanes

A Fourteenth Century Catalan Tomb at the Cloisters and Related Monuments - Rorimer, James J. (The Art Bulletin, 1931)
Keywords: bellpuig de las avellanes

A Monumental Catalan Wood Statue of the Fourteenth Century - Rorimer, James J. (Metropolitan Museum Studies, 1930)
Keywords: bellpuig de las avellanes